School principal’s role in increasing teachers’ pedagogical and professional competence in elementary schools in Indonesia - Ahmad Ansori; Suyatno Suyatno; Dwi Sulisworo (Jurnal Akuntabilitas Manajemen Pendidikan, 2021)
A principal has an important role in improving teacher’s competence. This qualitative research with a case study approach aimed to reveal school principal’s role in increasing teacher pedagogical and professional competence in Muhammadiyah elementary school of Macanan, Sleman and Muhammadiyah elementary school of Al-Mujahidin, Gunungkidul. The research subject was the school principal and teachers. Data were collected through observation, interview, and documentation, then were analyzed using the stages of data collection, data reduction, data representation, and conclusion drawing. The results show that the role of the school principal in increasing teacher pedagogical and professional competence was as a manager, leader, and innovator. As a manager, the school principal planned the program by detailing educators need and education staff, planning curriculum, and planning a policy for ad-ding the subject of guidance and counselling. As a leader, the school principal set the targets regarding class management and arranged a briefing, while as an innovator, the school principal emphasized the importance of innovation of information technology-based learning and class management. The three roles of the school principal impacted on teacher competence in conducting fun and meaningful learning, class management, the use of information technology in learning, the mastery of the material and student development. This research finding recommends Indonesia’s educational stakeholders to formulate the teacher’s competence development program.